Consolidation as a mechanism for word learning in sequential bilinguals. Issue 5 (30th November 2021) - Tartaro, Giacomo; Takashima, Atsuko; McQueen, James M.
Abstract: First-language research suggests that new words, after initial episodic-memory encoding, are consolidated and hence become lexically integrated. We asked here if lexical consolidation, about word forms and meanings, occurs in a second language. Italian–English sequential bilinguals learned novel English-like words (e.g., apricon, taught to mean "stapler"). fMRI analyses failed to reveal a predicted shift, after consolidation time, from hippocampal to temporal neocortical activity. In a pause-detection task, responses to existing phonological competitors of learned words (e.g., apricot for apricon ) were slowed down if the words had been learned two days earlier (i.e., after consolidation time) but not if they had been learned the same day. In a lexical-decision task, new words primed responses to semantically-related existing words (e.g., apricon-paper ) whether the words were learned that day or two days earlier. Consolidation appears to support integration of words into the bilingual lexicon, possibly more rapidly for meanings than for forms.